2015
DOI: 10.1007/s10266-015-0198-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and investigation of differentiation potential of human periodontal ligament cells and dental follicle progenitor cells and their response to BMP-7 in vitro

Abstract: The aim of this study was to assess the factors, mechanisms and the differences between periodontal ligament (PDL) cells and denta l follicle (DF) progenitor cells towards the osteoblastic/cementoblastic differentiation and to investigate the effects of BMP-7 on developmental (DF) and mature tissue-derived (PDL) cells, respectively. Primary cell culture of PDL cells and DF progenitor cells was performed. Osteogenic differentiation was evaluated using von Kossa, Alizarin Red S and immuno-histo-chemistry stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
0
13
1
Order By: Relevance
“…29 Yahya Acil et al also detected PDL cells were spindle-shaped and fibroblast-like. 30 Yuan Gao et al reported that the morphological characteristics of DSCs, GMSCs, and PDLSCs were similar. 10 In this current study, PDLMSCs and GMSCs met four criteria for being MSCs: (1) PDLMSCs and GMSCs adhered in cell culture flask after 24 hours (Figure 1).…”
Section: Discussionmentioning
confidence: 98%
“…29 Yahya Acil et al also detected PDL cells were spindle-shaped and fibroblast-like. 30 Yuan Gao et al reported that the morphological characteristics of DSCs, GMSCs, and PDLSCs were similar. 10 In this current study, PDLMSCs and GMSCs met four criteria for being MSCs: (1) PDLMSCs and GMSCs adhered in cell culture flask after 24 hours (Figure 1).…”
Section: Discussionmentioning
confidence: 98%
“…Briefly [31], impacted third molars were surgically extracted, and periodontal dental ligament was gently scraped from the middle root surface. Coronal and apical portions of the ligament were not used in order to avoid contamination by gingival and pulpal cells.…”
Section: Periodontal Ligamentmentioning
confidence: 99%
“…After digestion, tissue was seeded into culture flasks with alpha-modification of Eagle's Medium supplemented with 10% fetal bovine serum, 2-mM Glutamine, 100-U/mL penicillin and 100-μg/mL: streptomycin solution at 37°C in 5% CO 2 in a humidified atmosphere. After single cells were attached on the plastic bottom of the flask, non-adherent cells were removed by changing the medium [31].…”
Section: Periodontal Ligamentmentioning
confidence: 99%
“…These cells remodel the extracellular matrix (ECM), of which collagen fibers are the most prominent structures. PDL cells have been proposed as a source of mesenchymal stem cells (MSCs) . PDL cells possess characteristics of other stem cells, including: (i) a high level of MSC markers such as CD73, CD90 and CD105; (ii) self‐renewal capacity; and (iii) multilineage differentiation potential .…”
mentioning
confidence: 99%
“…PDL cells have been proposed as a source of mesenchymal stem cells (MSCs) . PDL cells possess characteristics of other stem cells, including: (i) a high level of MSC markers such as CD73, CD90 and CD105; (ii) self‐renewal capacity; and (iii) multilineage differentiation potential . Among tooth‐derived MSCs, PDL cells have been demonstrated to have a very high capacity to differentiate into mineral‐secreting cells in the presence of osteoinductive factors .…”
mentioning
confidence: 99%